Elicitor-Induced Biochemical and Molecular Manifestations to Improve Drought Tolerance in Rice (Oryza sativa L.) through Seed-Priming - Samota, Mahesh K.; Sasi, Minnu; Awana, Monika; Yadav, Om P.; Amitha Mithra, S. V.; Tyagi, Aruna; Kumar, Suresh; Singh, Archana (Frontiers in Plant Science, 2017)
Rice (Oryza sativa L.) is one of the major grain cereals of the Indian subcontinent which face water-deficit stress for their cultivation. Seed-priming has been reported to be a useful approach to complement stress responses in plants. In the present study, seed-priming with hormonal or chemical elicitor [viz. methyl jasmonate (MJ), salicylic acid (SA), paclobutrazol (PB)] showed significant increase in total phenolic content, antioxidant activity and expression of Rice Drought-responsive (RD1 and RD2) genes (of AP2/ERF family) in contrasting rice genotypes (Nagina-22, drought-tolerant and Pusa Sugandh-5, drought-sensitive) under drought stress. However, decrease in lipid peroxidation and protein oxidation was observed not only under the stress but also under control condition in the plants raised from primed seeds. Expression analyses of RD1 and RD2 genes showed upregulated expression in the plants raised from primed seeds under drought stress. Moreover, the RD2 gene and the drought-sensitive genotype showed better response than that of the RD1 gene and the drought-tolerant genotype in combating the effects of drought stress. Among the elicitors, MJ was found to be the most effective for seed-priming, followed by PB and SA. Growth and development of the plants raised from primed seeds were found to be better under control and drought stress conditions compared to that of the plants raised from unprimed seeds under the stress. The present study suggests that seed-priming could be one of the useful approaches to be explored toward the development of simple, cost-effective and farmer-friendly technology to enhance rice yield in rainfed areas.